The development of a tool to identify skilled meditators among meditation practitioners - 'The University of Colombo Intake Interview to identify Skilled Meditators for scientific research (UoC-IISM)' - N. O. Outschoorn; E. A. S. K. Somarathne; N. N. Dasanayaka; L. J. U. Karunarathne; K. K. Vithanage; K. P. C. Dalpatadu; E. Lokupitiya; M.W. Gunathunga; H. M. J. C. Herath; S. Jayasinghe; W. D. N. Dissanayake (College of Community Physicians of Sri Lanka, 2022)
Introduction: Buddhist-derived meditation is a well-known phenomenological practice that enhances overall wellbeing of individuals. However, broad- and less-rigorous criteria in recruiting suitable meditation practitioners affect the reliability of results obtained through meditation research. Objectives: To develop an instrument to identify skilled meditators among meditation practitioners, in order to use it in scientific research including medical research conducted to understand the physiological, psychological, social, and environmental effects of meditation Methods: Extensive literature reviews, interviews and focus group discussions with experts in a number of related fields were utilized in developing the instrument. Judgmental validation of the generated items was ensured through establishing their face, content and consensual validity. Internal consistency reliability and factor structure of the scale were explored to analyse its psychometric properties. Cut-off marks were determined to develop a scoring system for the instrument. Results: Twenty-five items were categorized under five sections (A, B, C1, C2, D) that addressed six factors: duration of the meditation practice, details of the meditation practice, peripheral awareness, stable attention, and alertness and emotional stability. Three further qualitative items were added under section E. An exploratory factor analysis process resulted in a two-factor structure between the Likert-scale items as theoretically expected. Scores to identify 'skilled meditators' were determined as: Section C1>7 (fall-back score; 7-9, ideal score; 10-12), Section C2>14 (fall-back score; 14-16, ideal score; 17-20) and Section D>25 (fall-back score; 25-29, ideal score; 30-35). Conclusions & Recommendations: The overall findings reveal the UoC-IISM to be a valid and reliable tool to be used in identifying skilled meditators, among meditation practitioners, for scientific research in the Sri Lankan context. The instrument explores six factors through its 28 items and the importance of using a combination of these factors is discussed.